Estrategias de marketing de la Veterinaria Smitty & Fluffy del cantón Simón Bolívar en el período 2023. - Jiménez García, Mayra Jesús (2025)
The present investigation is on the subject of marketing strategies of the Smitty & Fluffy veterinary clinic in the Simón Bolívar canton in the period 2023 that refers to La Veterinaria "Smith & Fluffy has a lot of potential due to having excellent qualified personnel, responsible for timely care of animals and the experience that precedes it, a situation is attributed to unassertive advertising, lack of updating of current media, and offering added value that gives the veterinary clinic the opportunity to be recognized as a brand and to have a differentiating factor from the competition that contributes to attracting new clients. As a result, the continuous increase in demand for animal health services has given rise to a significant market for veterinary care, which in turn has led to a significant increase in demand for veterinary services. In addition, the Smitty & Fluffy veterinary clinic needs to focus on the next generation and restructure marketing strategies to attract local clients and, through them, find potential clients that will allow the practice to grow, increasing the retention of current clients, as well as future patients. This project aims to take into consideration local information needs by seeking to obtain strategies that allow sustainable, accessible advertising with a high reach in digital media. Its main objective is to analyze the marketing strategies of the Smitty & Fluffy veterinary clinic in the Simón Bolívar canton to increase the visibility and recognition of the veterinary clinic through research techniques and the application of correct marketing strategies.